The effect of dietary astaxanthin and vitamin A supplementation on the reproductive performance of pond reared Penaeus monodon broodstock - Pangantihon, Ma. Paz Y. (College of Fisheries, University of the Philippines in the Visayas, 1989)
The effect of astaxanthin and/or vitamin A on the reproductive performance of pond reared Penaeusmonodon was assessed in a 2x2 factorial experiment. The study was conducted in four 12m3, 1 m deep flow-through maturation tanks divided into two equal compartments using a nylon net. Doubly tagged prawn broodstock were utilized as individual replicates.Prawns were fed with broodstock diet with no supplements (Treatment A), with astaxanthin (Treatment B, vitamin A (Treatment C) and both astaxanthin and vitamin A (Treatment D) for 61 days. Results showed mean gonad index., which measures the degree of gonadal development, was significantly improved (P-0.05) by astaxanthin supplementation. The interaction between astaxanthin and vitamin A was not significant (P.0.05). Fecundity and egg hatching rate were not significantly affected (P.0.05) by the addition of supplemental astaxanthin and/or vitamin A in the diet. Mean fecundity and hatching rate, however were highest in prawn fed astaxanthin supplements (7.3 x 104 eggs/female and 5.7% hatching) and lowest in prawn nofed any supplements (3.2 x 104 eggs/female and 0% hatching). Further, mortality rate was highest in prawns fed both astaxanthin and vitamin A supplements (50%) and lowest in prawns nt fed with any supplements. High mortality was attributed to the high levels of synthetic astaxanthin and vitamin A inclusion. The results suggest direct involvement of astaxanthin in gonadal development and spawning, and thus a dietary astaxanthin requirement for reproduction of pond reared Penaeusmonodon. Moreover, early maturation of some prawns fed astaxanthin supplement suggests its effect on hastening ovarian maturation even without eyestalk ablation.